Plankton community structure in mangrove ecosystem polluted by macroplastic waste Pagatan Besar Village, Tanah Laut Regency - Yunandar Yunandar; Nur Fadhilah Rahim; Rahmiati Rahmiati; Gidion Caraka; Edi Rusdiyanto (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2024)
Plastic waste continues to increase all the time without decreasing or ending, resulting in the sustainability and restoration of the mangrove ecosystem needing to be improved. The mangrove ecosystem is a place where plastic waste accumulates. The accumulation of plastic waste prevents photosynthesis in mangroves, reduces aquatic productivity and encourages microbial colonization. This research aims to identify the type abundance of plankton, waste and water quality. Sampling was carried out purposively from June to July 2023. STA 1 represents rivers, STA 2 was estuaries and STA 3 was coastal mangroves. Plankton, plastic waste and water quality samples were collected at the beginning of each month based on a 1x1 m2 plot. Furthermore, biological index calculations of plankton and the density of plastic waste were carried out and their relationship with water quality in each location. Mangroves in the village of Pagatan Besar are dominated by Avicennia marina, Avicennia alba, Bruguierra cylindrica and Rhizopora apiculata. The highest density of was in STA 3, but it was inversely proportional to the abundance and diversity of plankton due to the dense waste cover between the roots, mainly plastic materials. The most significant increase in marine waste accumulated in STA 3 from 6697 grams at the beginning of the observation to 13820 grams. The most significant composition of waste in STA 3 consists of plastic bottles and plastic cups. Cyanophyta, Chlorophyta and Chrysophyta are plankton phyla from the research location. Plankton identified there are three phyla in STA 1 and STA 2, while in STA 3, there are only 2. Cyanophyta, Chlorophyta and Chrysophyta are phyla plankton from the study site. The types of plankton that are always present in all STAs are Gonatozygon and Ulothrix from Chloropyta. The survival of plankton and mangroves is influenced by water temperature, pH, salinity, dissolved oxygen and the type of material density of macroplastic waste.Keywords:MacroplasticMangroveWater QualityPlankton